A magyar adórendszer egyszerűsítésének okai és lehetséges hatásai - Gáspár, Andrea (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
There are nearly 50 different tax categories in an effect currently in Hungary. These request a different acknowledgement, in payment deadline doing the dirty of the taxpayers. Hungary occupies the 111. place in a hierarchy classifying the simplicity of the taxation according to the study of tax payment with 2009 titles prepared by IFC between the exam-ined 181 countries. I examined it in my analysis in our taxation ensued changes. The changes complicated our fiscal system in some cases. But there is a tax category like that pi. personal income tax, where 4,6, there were 2 tax brackets in validity then. It continued with "Eva", "Ekho" introduction then simplification, which all of them are until the today’s day continuously on an agenda, yes. International - European Union ensued in his member states mainly - examining tendencies it adapting opportunity and I deducted my inferences analyzing its possible effects onto the Hungarian tax brackets and tax categories.